2012
DOI: 10.1111/j.1469-8137.2012.04210.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of new type III effectors from Xanthomonas uncovers XopB and XopS as suppressors of plant immunity

Abstract: Summary The pathogenicity of the Gram‐negative plant‐pathogenic bacterium Xanthomonas campestris pv. vesicatoria (Xcv) is dependent on type III effectors (T3Es) that are injected into plant cells by a type III secretion system and interfere with cellular processes to the benefit of the pathogen. In this study, we analyzed eight T3Es from Xcv strain 85‐10, six of which were newly identified effectors. Genetic studies and protoplast expression assays revealed that XopB and XopS contribute to disease symptoms an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(106 citation statements)
references
References 113 publications
(281 reference statements)
6
99
1
Order By: Relevance
“…A number of genes described previously as involved in incompatible plant-pathogen interactions were found to be specifically induced during ETI, supporting the idea that gene expression differences are a useful way to distinguish the two immune responses [9]. Several previous studies have used reporter genes as a readout for activation of PTI and its subsequent suppression by pathogen effectors [44][45][46][47]. Reporter genes for PTI have also been developed for tomato and N. benthamiana [5,48,49].…”
Section: Discussionmentioning
confidence: 72%
“…A number of genes described previously as involved in incompatible plant-pathogen interactions were found to be specifically induced during ETI, supporting the idea that gene expression differences are a useful way to distinguish the two immune responses [9]. Several previous studies have used reporter genes as a readout for activation of PTI and its subsequent suppression by pathogen effectors [44][45][46][47]. Reporter genes for PTI have also been developed for tomato and N. benthamiana [5,48,49].…”
Section: Discussionmentioning
confidence: 72%
“…vesicatoria, we performed transcript studies with strains 85-10 and 85-10hrpG* (85*), which contains HrpG*, a constitutively active version of HrpG (49). HrpG is the key regulator of the T3S genes and also activates the expression of T2S genes (8,(50)(51)(52). Yet, the expression of the T2S substrate gene XCV0965 is suppressed by HrpG, as was shown in our previous study (8).…”
Section: Resultsmentioning
confidence: 82%
“…This phenotype demonstrates the importance of a pathogen's ability to establish infection for overall virulence. While XopK is a predicted T3E effector that carries the hallmarks of a secreted virulence factor (Furutani et al, 2006;Furutani et al, 2009;Schulze et al, 2012), its roles during infection appear to be complex. The XopK protein sequence contains 54% hydrophobic residues and several predicted transmembrane domains.…”
Section: Discussionmentioning
confidence: 99%
“…Previous data indicated that XopK is secreted through the type III secretion system into host cells (Furutani et al, 2009;Schulze et al, 2012). Although the xopK gene is conserved in many Xanthomonas species, its role in virulence is unknown (Bogdanove et al, 2011;Potnis et al, 2011;Bart et al, 2012;Schulze et al, 2012;Arrieta-Ortiz et al, 2013;Jalan et al, 2013).…”
mentioning
confidence: 99%